2008
DOI: 10.1038/bjp.2008.189
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inhibition of the Na+/H+‐ exchanger causes regression of hypertrophy, heart failure, and ionic and electrophysiological remodelling

Abstract: Background and purpose: Increased activity of the Na þ /H þ -exchanger (NHE-1) in heart failure underlies raised [Na þ ] i causing disturbances of calcium handling. Inhibition of NHE-1, initiated at the onset of pressure/volume overload, prevents development of hypertrophy, heart failure and remodelling. We hypothesized that chronic inhibition of NHE-1, initiated at a later stage, would induce regression of hypertrophy, heart failure, and ionic and electrophysiological remodelling. Experimental approach: Devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
82
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 36 publications
7
82
0
3
Order By: Relevance
“…These results suggest that an increase in NHE-1 density could persist during the development of cardiomyopathy and continue to contribute to the development of cardiac lesions leading to HF and early death of HCMHs. These results are in agreement with various lines of evidence showing the involvement of NHE-1 in cardiac pathologies related to increases of [Na + ] i and [Ca 2+ ] i levels, such as in hypertrophy and HF leading to early death (Engelhardt et al 2002;Chahine et al 2005;Darmellah et al 2007;Baartscheer et al 2008;Karmazyn et al 2008Karmazyn et al , 1999. In line with the latter results, a recent study using a rabbit HF model showed that cariporide treatment for 2 months following the development of cardiac hypertrophy restored cardiomyocyte [Na + ] i and [Ca 2+ ] i handling, and reduced hypertrophy and signs of HF (Baartscheer et al 2008).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results suggest that an increase in NHE-1 density could persist during the development of cardiomyopathy and continue to contribute to the development of cardiac lesions leading to HF and early death of HCMHs. These results are in agreement with various lines of evidence showing the involvement of NHE-1 in cardiac pathologies related to increases of [Na + ] i and [Ca 2+ ] i levels, such as in hypertrophy and HF leading to early death (Engelhardt et al 2002;Chahine et al 2005;Darmellah et al 2007;Baartscheer et al 2008;Karmazyn et al 2008Karmazyn et al , 1999. In line with the latter results, a recent study using a rabbit HF model showed that cariporide treatment for 2 months following the development of cardiac hypertrophy restored cardiomyocyte [Na + ] i and [Ca 2+ ] i handling, and reduced hypertrophy and signs of HF (Baartscheer et al 2008).…”
Section: Discussionsupporting
confidence: 92%
“…In these pathologies, overload of intracellular Na + ([Na + ] i ) was also reported (Meng and Pierce 1991;Bkaily and Jacques 1994;Karmazyn 2001;Karmazyn et al 2003;Chahine et al 2005;Cingolani and Ennis 2007), which could be due, in part, to an increase in Na + influx caused by upregulation of cardiac Na + -H + exchanger isoform-1 (NHE-1) activity (Meng and Pierce 1991;Karmazyn 2001;Karmazyn et al 2003;Cingolani and Ennis 2007). This sodium overload could consequently lead to a calcium overload due to the increased activity of the sodium-calcium exchanger (NCX) (Chahine et al 2005;Baartscheer et al 2008). Studies using animal models of HF (Yoshida and Karmazyn 2000;Engelhardt et al 2002;Loennechen et al 2002;Chen et al 2004;Baartscheer et al 2008;Karmazyn et al 2008) as well as isolated cardiomyocytes (Karmazyn et al 2003) have demonstrated the beneficial effect of NHE-1 blockade in preventing cardiac hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies also showed that the inhibition of NHE1 by inhibitors attenuated the hypertrophy of cardiomyocytes (23)(24)(25)(26)(27). Because we also found a significant decrease in the medial wall thickness of pulmonary arteries in NHE1-deficient mice with decreased hypoxic pulmonary hypertension and vascular remodeling (11), we hypothesized that the effects of NHE1 on hypoxia-induced PASMC hypertrophy were also mediated via E2F1.…”
mentioning
confidence: 71%
“…Studies indicated the relationship between NHE1 and myocardial hypertrophy, showing that the inhibition of NHE1 activity by inhibitors reduced cardiac hypertrophy in animals and cultured cardiomyocytes (23)(24)(25)(26)(27). The increased medial wall thickness of pulmonary arteries in pulmonary hypertension and vascular remodeling is involved not only in the proliferation of PASMCs, but also in the hypertrophy of PASMCs.…”
Section: Discussionmentioning
confidence: 99%